A Legal and Cultural Comparison of File-Sharing Disputes in Japan and the Republic of Korea and Implications for Future Cyber-Regulation - Letiner, John (Columbia Journal of Asian Law, 2008)
Japan and the Republic of Korea (“Korea”) are large, international markets for the entertainment industry, and both nations have experienced legal and social battles relating to the introduction and growing popularity of file-sharing technology. During the past few years, civil lawsuits and criminal charges have been brought in Japan and Korea in an effort to combat online sharing of copyrighted works. The provider of the first major Japanese file-sharing service, File Rogue, was found civilly liable for copyright infringement. The Japanese programmer of the popular file-sharing software, Winny, was convicted of the crime of aiding and abetting copyright violations. In Korea, legal action has taken the form of civil litigation against the providers of Soribada, the “Korean Napster,” and some criminal prosecutions of individual end users who shared copyrighted works. While both Japanese and Korean owners of copyrighted content have litigated aggressively against providers of file-sharing services, there is reason to believe that each nation may have reached the limit of its socially acceptable legal options for combating file-sharing. Present conditions suggest that file-sharing will persist in both nations, but the frequency of file-sharing and its impact on the entertainment industry have been and will continue to be greater in Korea. Korea and Japan present an interesting comparison because they share a number of significant similarities related to file-sharing. First, until 1957, Korean copyright law was substantively the same as Japanese copyright law. The formal copyright provisions in the two nations remain quite similar. The economies and legal regimes of both nations developed (or at least re-developed) largely during the second half of the twentieth century, so as societies in economic transition both have recently experienced challenges in formulating their intellectual property policies. Further, both nations are highly “wired” and have relatively high levels of internet connectivity and broadband access as compared to other nations. Despite these similarities, however, file-sharing has been more pervasive in Korea. Not surprisingly, Japanese file-sharing has not been alleged to have caused the dramatic financial losses to the Japanese music industry that the Korean music industry has experienced (and blames on file-sharing). The differences in file-sharing rates and probable effects can be partially attributed to subtle differences in the formal copyright law of Japan that have mitigated the economic effects of file-sharing and affected the decision-making of prospective Japanese file-sharers. Notably, it has been legal provisions generally disfavored by the entertainment industry, such as permitting CD rentals, and not stronger punitive measures against file-sharers, that have lessened the impact of file-sharing on Japanese copyright owners. For Korea, where file-sharing has been and remains common and economically significant, a broader consideration of the cultural environment is necessary. While cultural issues are at play in explaining the consistent pervasiveness of file-sharing even in the face of criminal sanctions, the operative factors are not traditional Confucianist notions, as are often invoked to explain social attitudes in East Asia. Rather, more recent Korean cultural factors offer insight into the society’s file-sharing activities. To evaluate the similarities and differences between file-sharing law and practice in Japan and Korea, I will first describe the relevant law in both nations and then summarize their experiences with file-sharing. This summary includes a discussion of relevant law and cases, results of interviews with file-sharers in Japan and Korea, and commentary upon profit trends in the music industry. I will then evaluate the key distinctions in law and culture that have shaped the trajectory of file-sharing in both nations. Relevant legal distinctions include Japan’s music rental industry and its statutory private copying exemption compensation system. These legal policies simultaneously compelled the Japanese music industry to adapt quickly to the challenges of the digital age and mitigated the economic impact of file-sharing and other copying. Cultural issues include the differing rates of internet access between the Japanese and Korean populaces, distinctive recent historical experiences of copyright law, and the unique role of the internet in Korean social and political life. Based on these distinctions, I will explain some of the differences in file-sharing activities and legal regulation in Japan and Korea and offer predictions about the course of the file-sharing debate in both nations in the future. The dynamics of both nations suggest that strict enforcement of present copyright law is not practical, and in any event such enforcement would not be sufficient to counter file-sharing. Innovative legal and private industry solutions play a growing role in protecting the economic interests of the Japanese and Korean entertainment industries and will remain necessary to balance the interests of copyright holders against the preferences and behaviors of individual consumers. While these considerations bear most directly upon the nations of Korea and Japan, it is useful for other nations, especially ones with large entertainment industries such as the United States of America (the “U.S.”), to consider the legal strategies and cultural forces shaping the file-sharing debate in these highly internet-connected and heavy entertainment consuming nations.